Medical Informatics Specialists: What Are their Job Profiles? - Knaup, P.; Frey, W.; Haux, R.; Leven, F. J. (Methods of Information in Medicine, 2003)
Objectives: Since 1972, the University of Heidelberg and the University of Applied Sciences Heilbronn have jointly been running a medical informatics program. To continuously provide high quality education, the curriculum is regularly evaluated among its graduates. The objectives of this study were to assess the job situation of the graduates and to evaluate the curriculum from their viewpoint.Method: Anonymous inquiry of all medical informatics graduates, having finished their studies before March 31, 2001 (n = 1024) using a structured questionnaire.Results: The questionnaire was answered by 446 (compliance: 45.5%) graduates. About one third (146 of 444 valid cases) are working in software/ hardware companies. 179 (43.0% of 416 valid cases) graduates are working within medical informatics, 214 (51.4%) are working outside of medical informatics, but within other informatics. 23 (5.5%) graduates are working neither in medical nor in other informatics. 15 percent of the responding graduates have received a doctor’s degree. Software engineering, database and information systems are regarded as most important parts of the education. The majority of the graduates are satisfied with their education as well as with their personal career.Conclusions: The variety of jobs, the job profiles, and the high level of our graduates’ satisfaction with their education indicate the relevance of specialized medical informatics programs with a curricular profile like the one in Heidelberg/Heilbronn. Investigations like this can help to adjust the contents of the curriculum to professional needs.
Keywords: Medical informatics; health informatics; education